Efficient removal of cathepsin L from active cathepsin X using immunoprecipitation technique - Pečar Fonović, Urša (Acta chimica slovenica, 2009)
Cathepsin X is a cysteine protease which is involved in various important physiological and pathological processes. For the purpose of biochemical and structural studies, pure and active cathepsin X is required without contamination with other related proteases. Recombinant cathepsin X was obtained by expression in methylotropic yeast Pichia pastoris. During purification, cathepsin X has to be activated with cysteine protease cathepsinL, however, separation methods, used so far, can not completely remove cathepsin L from the activated cathepsin X. Here we describe a new purification procedure which provides active recombinant cathepsin X without the presence of residual cathepsin L.
Keywords: biokemija; cisteinske proteaze; čiščenje; izolacija; katepsin